2006
DOI: 10.1002/jms.1105
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectra of divalent metal ion adducts of glycosyl sulfides, sulfoxides and sulfones; distinction among stereoisomers

Abstract: The tandem mass spectra of the divalent metal ion (Mg2+, Ca2+, Sr2+, Ba2+, Mn2+, Ni2+, Co2+ and Zn2+) adducts of acetylated 1,2-trans-glycosyl sulfides, sulfoxides and sulfones were examined using low energy collision-induced dissociation on a Quattro II quadrupole tandem mass spectrometer. Abundant doubly charged ions, such as [3M + Met]2+ and [2M + Met]2+, were observed with alkaline earth metal chlorides. The other ions observed were [M + MetCl]+, [M + MetOAc]+, [M + MetO2SPh]+ and [2M + MetCl]+. The deprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Some earlier studies also showed that simple metal‐cationized monomeric or dimeric compounds exhibit stereoisomeric distinction when subjected to CID 50–53. For example, Fe 2+ ions have been used to form regioselective and stereoselective transition metal complexes and characteristic product ions by CID for structural elucidation of carbohydrates 50, 51.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some earlier studies also showed that simple metal‐cationized monomeric or dimeric compounds exhibit stereoisomeric distinction when subjected to CID 50–53. For example, Fe 2+ ions have been used to form regioselective and stereoselective transition metal complexes and characteristic product ions by CID for structural elucidation of carbohydrates 50, 51.…”
Section: Methodsmentioning
confidence: 99%
“…Some earlier studies also showed that simple metalcationized monomeric or dimeric compounds exhibit stereoisomeric distinction when subjected to CID. [50][51][52][53] For example, Fe 2þ ions have been used to form regioselective and stereoselective transition metal complexes and characteristic product ions by CID for structural elucidation of carbohydrates. 50,51 Stereoisomeric differentiation of glycosyl dithioacetals, sulfides, sulfoxides and sulfones has also been successful using different transition-metal ion adducts and tandem mass spectrometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…330 Aggarwal and colleagues 331,332 have undertaken the preparation and characterization of 234 U and of working standards for 238 Pu. They have applied GC-MS for the determination of Pb in blood and urine, of Hg in blood and of Te (Te from the antitumor drug AS-101) in urine, using stable isotopes ( 196 Hg,120 Te, 204 Pb) derivatized with appropriate chelating reagents. [333][334][335][336] Geochronological studies 40 Ar- 39 Ar dating of Siberian basaltic volcanism; Sm-Nd dating of Archean metavolcanics of the Dharwar Craton; Sm-Nd and Rb-Sr dating and P-T history of the Archean Sittampundi and Bhavani layered meta-northosite complexes in the Cauvery shear zone.…”
Section: Nuclear Chemistrymentioning
confidence: 99%
“…The hexose units in Me-glucoside, mannoside and galactoside could also be identified accurately. [120][121][122] Analysis of proscribed chemicals A significant contribution of Vairamani and colleagues was the establishment of the Centre for the Analysis of Chemical Toxins (CACT) at IICT. This centre is one of the 18 laboratories globally designated by the Organization for the Prohibition of Chemical Weapons (OPCW) for the off-site analysis of scheduled chemicals, prohibited under the Chemical Weapons Convention (CWC).…”
Section: Introductionmentioning
confidence: 99%